AN INTERVAL-VALUED SPHERICAL FUZZY SWARA-CRADIS APPROACH TO STRATEGIC PROBLEM-SOLVING IN LOCAL MEDIA BUSINESSES - SARIGÜL MERT, Aleyna; AYTEKİN, Ahmet (Journal of process management and new technologies, 2025)
This research aims to identify the key challenges faced by local media businesses, assess their severity, and propose strategic solutions. As social media and technological advancements continue to transform the media landscape, local media organizations are struggling with a wide range of problems. However, most existing strategies have failed to achieve their intended outcomes. The study employs a two-stage data collection process conducted in Artvin province, Turkey. In the first stage, the main challenges and potential strategic solutions were identified based on expert opinions. The problems of local media companies were categorized under the following dimensions: economic issues, technological and digital infrastructure, employment and skilled personnel shortages, structural and institutional challenges, legal and administrative barriers, content production and journalistic quality, distribution and accessibility, and media–political relations and ethical concerns. In the second stage, these problems and strategic solution proposals were evaluated based on experts’ assessments using the Interval-Valued Spherical Fuzzy SWARA-CRADIS methodology. The findings indicate that local media businesses struggle not only with limited economic resources but also with difficult working conditions, insufficient leave, excessive workloads, and the migration of qualified personnel. The proposed strategic solutions focus on strengthening legal and regulatory support, focusing on local community engagement, and enhancing accessibility and content diversity.